Efficacy and safety analysis of midazolam combined with dezocine sedation and analgesia colonoscopy in patients with inflammatory bowel disease: a prospective single-center open study - Chen, Yongpeng; Lu, Yi; Xiang, Xueyuan; Fu, Liping; Liu, Yanan; Li, Chujun; Sun, Jiachen (Frontiers in Pharmacology, 2023)
Abstract：Objective: Colonoscopy plays an important role in the diagnosis, prognosis prediction, assessment of disease activity and severity, and treatment of inflammatory bowel disease (IBD)related complications. However, some patients refuse to undergo colonoscopy due to perceived pain and other discomfort, their diagnosis and treatment are affected. Therefore, we conducted a prospective study to explore the efficacy and safety of midazolam combined with dezocine for sedation in IBD patients undergoing colonoscopy. Methods: 224 patients were divided into sedativecolonoscopy-group (SCG, n=93), anesthesia-colonoscopy-group (ACG, n=90) and ordinarycolonoscopy-group (OCG, n=41). The-vital-signs (blood pressure, pulse, respiration and blood oxygen saturation), pain degree during colonoscopy, satisfaction and complication rates of the three groups were compared. Results: Before colonoscopy, there was no significant difference among the vital signs of the three groups. The vital signs of the ACG were significantly lower than those of the SEG and the OCG (p<0.05), and the difference was not significant between the SCG and OCG Running Title 2 during colonoscopy. The colonoscopy pain score in the SCG was lower than that in the OCG (0.79 ± 1.09 vs. 2.98 ± 1.27, p<0.001). The satisfaction score of the SCG (9.26 ± 1.16) was not significantly different from that of the ACG (9.42 ± 1.41) but was higher than that of the OCG (6.63 ± 1.13) (p<0.001). The total complication rate of the ACG was 45.56% (41/90), which was significantly higher than that of the SCG [20.43% (19/93)] and the OCG [19.51% (8/41)]. Colon perforation, abnormal blood pressure fluctuation and hypoxemia were significantly more common in the ACG than in the SCG and the OCG (p<0.05). However, there was no significant difference in the incidence of complications between the SCG and OCG. Conclusion: Compared with ordinarycolonoscopy, colonoscopy performed under midazolam and dezocine sedation is more comfortable for patients, thereby increasing satisfaction and compliance. Colonoscopy that is performed under midazolam and dezocine is similar to colonoscopy that is anesthesia with propofol in terms of comfort, satisfaction and compliance and similar to ordinary-colonoscopy in terms of safety.Considering the shortage of anesthesiologists, the application of midazolam combined with dezocine for digestive endoscopy is worthy of clinical promotion.